Charcoal producers and the pandemic: effects of COVID-19 in Pokot Central, Kenya - Petersen, Maike; Kamurio, Chebet N.; Kortom, Chepkemoi D.; Nüsser, Marcus (Erdkunde, 2021)
When the COVID-19 pandemic unfolded, public health measures were implemented globally. Early on, concerns grew that lockdowns and travel restrictions could have severe consequences, especially for marginalized communities in the Global South. In Sub-Saharan Africa, wood charcoal is not only an important cooking fuel, but provides income for many rural households. Despite its economic value, the charcoal sector is, however, largely unregulated and viewed exclusively as an environmentally damaging industry by policy makers and the public who make it responsible for large-scale deforestation. The present study employs a sustainable livelihood framework to assess the ability of charcoal producers in northwestern Kenya, to cope with a short-term shock such as the COVID-19 pandemic and preventive measures. It furthermore compares their access to health information to that of non-producers. A street survey of 139 respondents allowed to gain rapid insights into the realities of a group not accessible via online or telephone surveys. The results show that 87 % of charcoal producers face severe decline of this economic practice because of limited market access. These losses cause them food insecurities, while non-charcoal producers are more worried about social consequences of the restrictions. Though charcoal producers and non-producers feel equally well informed about the pandemic, producers are less likely to access reliable information channels than non-producers, resulting in an uneven distribution of health information across the community. By investigating the response of producers to an external shock and limited market access this study adds to the understanding of local vulnerabilities and the sustainability of rural livelihood strategies. This research argues for inclusive policy response to ensure consideration of the informal sector in crisis response as well as to provide adequate and low-threshold access to health information.